Changes in Mortality Involving Extended-Release and Long-Acting Opioids After Implementation of a Risk Evaluation and Mitigation Strategy. Issue 1 (16th March 2019) - Black, Joshua C; Bau, Gabrielle E; Rosen, Travis; Cepeda, M Soledad; Wedin, Gregory P; Green, Jody L; Dart, Richard C
Abstract: Objective: To assess changes in mortality rates in extended-release and long-acting (ER/LA) opioid analgesics after the implementation of the Risk Evaluation and Mitigation Strategy (REMS). Setting: All drug poisoning deaths in three states: Florida, Oregon, and Washington. Data were obtained through state vital records offices and the Researched Abuse, Diversion and Addiction-Related Surveillance System Medical Examiner Program. Methods: Using cause-of-death literal text from death certificates, individual opioid active pharmaceutical ingredients (APIs) involved in each death were identified using rules-based natural language processing. Population-adjusted and prescriptions dispensed–adjusted mortality rates were calculated for all ER/LA opioid analgesic and individual opioid APIs. Rates before and after implementation of the REMS were compared. Rate changes were compared with rates from two APIs with little or no inclusion in the REMS: benzodiazepines and hydrocodone. Results: The mean ER/LA opioid analgesic population-adjusted mortality rate significantly decreased in all three states (FL: P =  0.003; OR: P  =   0.003; WA: P  < 0.001). Mortality rates for benzodiazepines and hydrocodone also decreased and were not statistically different. Significant heterogeneity in mortality rates of individual opioids was observed between the three states. When adjusted for prescription volume, the ER/LA opioid analgesic mortality rate decreased in all three states, but was significant only for Washington ( P  <   0.001). Conclusions: The population-adjusted mortality rate of ER/LA opioid analgesics has decreased in three states. Notably, the contributions to mortality rates by individual opioid analgesics were not uniform across the three states in this study. However, these changes were not generally distinct from changes in mortality rates where comparator substances were involved.